Konsep Diri, Intensitas Komunikasi Orang Tua-Anak, dan Kecenderungan Perilaku Seks Pranikah - Munawaroh, Faizatul (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract. This study aimed to explore the relationship between self-concept and the intensity of parent-child communication with premarital sex trend. Total subjecs of study were 97 students aged 17-19 years, consisted of 31 male students and 66 female. The data was collected using a scale of 3 pieces each scale trend of premarital sex, self-concept and the intensity of communication among parents and children.The collected data were analyzed with a statistical technique of regression analysis and then parcial correlation. Results of analysis of data showed no significant association between self-concept and the intensity of parent-child communication with the trend of premarital sex. The results of partial analysis showed  no  correlation between self-concept and tendency of premarital sex behavior. There was a negative correlation between the intensity of parent-child communication and the tendency of premarital sex. Key words:  premarital sex behavior, self-concept, intensity of parent-child communication.